Procurement process and financial performance: a systematic literature review - Georgino, Mônica; Alcantara, Rosane Lucia Chicarelli; Albuquerque, Andrei Aparecido de (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – The aim of this study was to identify the elements and practices under the responsibility of the Procurement process that can influence the financial performance of a company. Design/methodology/approach - A Systematic Literature Review (SLR) was conducted to identify the elements and practices from the Procurement process and financial indicators. Findings - Twelve elements were identified (focusing on: Information technology and shared information and communications) and eight practices in the procurement process (focusing on: supplier relationship management and cost reduction), which contributes to the company’s financial performance, mainly on the Profit and ROI financial indicators. Originality/value - This study presents an overview, a consolidated view of the literature on the current relationship between the procurement process and financial performance. Keywords – Procurement. Financial Performance. Systematic Literature Review. Elements. Practices.